Taking stock of vaccine hesitancy among migrants: a scoping review protocol - Charles S Wiysonge; Sten H Vermund; Akhenaten Siankam Tankwanchi; Anelisa Jaca; Heidi J Larson (BMJ Open)
Introduction At the 72nd World Health Assembly of May 2019, WHO member states prioritised a global action plan to promote migrant and refugee health. Five months earlier, WHO had declared vaccine hesitancy—the reluctance to vaccinate despite the availability of vaccination services—as one of the top 10 threats to global health. Although vaccination is often a requirement for immigration, repeated outbreaks of vaccine-preventable diseases within certain immigrant communities in some host nations suggest that vaccine hesitancy could be a factor in their susceptibility to vaccine-preventable diseases. Studies of the prevalence and determinants of vaccine hesitancy among migrants globally seem to be lacking. This scoping review will (1) identify articles on vaccine hesitancy among migrants; (2) examine the extent and nature of the extant evidence; and (3) determine the value of undertaking a full systematic review.Methods and analysis The framework for the scoping review proposed by the Joanna Briggs Institute will be used. The reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. Studies published in English or French between January 1999 and December 2019 will be drawn from most or all of the following multidisciplinary databases: Africa-Wide Information, Allied and Complementary Medicine, Cochrane Library, Cumulative Index of Nursing and Allied Health Literature, Embase, Index Medicus for the Eastern Mediterranean Region, International Bibliography of Social Sciences, Literature in the Health Sciences in Latin America and the Caribbean, Medline, Proquest Theses/Dissertations, PsycInfo and Web of Science. The search will include an extensive list of keywords to capture multiple dimensions of confidence and hesitancy vis-à-vis vaccines among migrants. Findings will be reported through summary narratives, tables, flowcharts and evidence maps.Ethics and dissemination This review is exempted from ethical approval and will be published in a peer-reviewed open-access journal to ensure wide dissemination.